Technical Packages in Injury and Violence Prevention to Move Evidence Into Practice: Systematic Reviews and Beyond. (February 2017) - Haegerich, Tamara M.; David-Ferdon, Corinne; Noonan, Rita K.; Manns, Brian J.; Billie, Holly C.
Injury and violence prevention strategies have greater potential for impact when they are based on scientific evidence. Systematic reviews of the scientific evidence can contribute key information about which policies and programs might have the greatest impact when implemented. However, systematic reviews have limitations, such as lack of implementation guidance and contextual information, that can limit the application of knowledge. "Technical packages, " developed by knowledge brokers such as the federal government, nonprofit agencies, and academic institutions, have the potential to be an efficient mechanism for making information from systematic reviews actionable. Technical packages provide information about specific evidence-based prevention strategies, along with the estimated costs and impacts, and include accompanying implementation and evaluation guidance to facilitate adoption, implementation, and performance measurement. We describe how systematic reviews can inform the development of technical packages for practitioners, provide examples of technical packages in injury and violence prevention, and explain how enhancing review methods and reporting could facilitate the use and applicability of scientific evidence.